Malabaricane and Isomalabaricane Triterpenoids, Including Their Glycoconjugated Forms - Valentin A. Stonik; Sophia A. Kolesnikova (Marine Drugs, 2021)
In this review, we discuss structural diversity, taxonomic distribution, biological activities, biogenesis, and synthesis of a rare group of terpenoids, the so-called malabaricane and isomalabaricane triterpenoids, as well as some compounds derived from them. Representatives of these groups were found in some higher and lower terrestrial plants, as well as in some fungi, and in a relatively small group of marine sponges. The skeletal systems of malabaricanes and isomalabaricanes are similar to each other, but differ principally in the stereochemistry of their tricyclic core fragments, consisting of two six-membered and one five-membered rings. Evolution of these triterpenoids provides variety of rearranged, oxidized, and glycoconjugated products. These natural compounds have attracted a lot of attention for their biosynthetic origin and biological activity, especially for their extremely high cytotoxicity against tumor cells as well as promising neuroprotective properties in nanomolar concentrations.